2020
DOI: 10.1002/eat.23241
|View full text |Cite
|
Sign up to set email alerts
|

Temperament in preadolescence is associated with weight and eating pathology in young adulthood

Abstract: Objective: Few longitudinal studies have investigated the role of temperament traits on weight and eating problems thus far. We investigated whether temperament in preadolescence influences body weight and the development of eating pathology in adolescence and young adulthood. Method: This study used data from TRAILS (Tracking Adolescents' Individual Lives Survey), a Dutch community cohort study (N = 2,230) from preadolescence into adulthood. At age 11, the temperament dimensions negative affectivity and effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…Although there has been a recent increase in studies investigating the effects of temperament types on the risk of obesity development, these studies have often focused on children (9,15). In adults, neurotic personality trait is associated with higher body mass index (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there has been a recent increase in studies investigating the effects of temperament types on the risk of obesity development, these studies have often focused on children (9,15). In adults, neurotic personality trait is associated with higher body mass index (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Temperament types are associated with whether preschool children eat breakfast (12). Negative emotionality in adolescence is identi ed as a risk factor for disordered eating behaviors and attitudes (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between temperament and EMS is well established (Halvorsen et al, 2009; Haugh et al, 2017), but it was interesting that negative affect and effortful control were the only temperament factors found to be a strong predictor of EMS in our model. Although it did not measure EMS, one study measured temperament at preadolescence and the presence of EDs in young adulthood, finding that higher levels of negative affect and lower effortful control were related to higher BMI and higher levels of eating pathology (Eeden et al, 2020). Negative affectivity encompasses the trait of neuroticism, a factor that previous studies have found to be a risk factor in the development of EDs (Brown et al, 2020; Lee‐Winn et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This 22‐item self‐report questionnaire generates an overall symptom composite score that indicates the level of eating pathology, not the specific type of eating disorder problems (Krabbenborg et al, 2012 ; Stice, Fisher, & Martinez, 2004 ; Stice, Telch, & Rizvi, 2000 ). When at least half of the required items had been answered, the EDDS standardized score (ranging from 0 to 100) was constructed by summing standardized item scores, excluding items regarding height, weight, amenorrhea and use of birth control (van Eeden, Hoek, van Hoeken, Deen, & Oldehinkel, 2020 ). The internal consistency of the EDDS score has been shown to be satisfactory (Stice et al, 2004 ), and the EDDS score correlates strongly ( r = 0.85, p < .001) with the symptom composite score of the EDE (Fairburn et al, 2008 ; Krabbenborg et al, 2012 ), the most frequently used questionnaire for examining eating disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Each item could be rated on a 5‐point scale ranging from 1 (“hardly ever true”) to 5 (“almost always true”). Mean scores for negative affectivity were calculated when at least half of the items had been answered (van Eeden et al, 2020 ). The mean score of the parental and children's scores together was used in this study.…”
Section: Methodsmentioning
confidence: 99%